Postbiotic effects of Enterococcus faecium JB00008 on gut health and IBD vaccination in broiler chickens - Seonju Lee; Seojin Choi; Jongbin Park; Biao Xuan; Eun Bae Kim (PLoS ONE, 2026)
Feeding various probiotic lactic acid bacteria, including Enterococcus faecium , can alleviate intestinal inflammation and improve gut health in animals. Recently, postbiotics—non-living preparations derived from microbial cells or their metabolites—have gained attention. However, studies on the effects of these postbiotics on immune markers and changes in the gut microbiota of chickens are limited. In this study, we evaluated the effects of the probiotic strain E. faecium JB00008 on the chicken intestinal tract and characterized immune markers and gut microbiota following viral vaccination. Chicks were divided into three groups (Control, DH5α, and JB00008) and administered the respective supernatants in drinking water from days 1–12 at a 3:7 ratio. Samples were collected on days 13 and 28 for microbiota and gene expression analyses. To immunize against infectious bursal disease (IBD), the chicks received an oral vaccine on day 13. Growth, immune, and gut parameters were measured. Body weights did not differ among groups ( p = 0.380). Several intestinal immune markers—mucin 2 ( MUC2 , p = 0.001), occludin ( OCLN , p < 0.001), and interleukin-10 ( IL-10 , p < 0.001)—were significantly higher in the JB00008 group. Annexin A5 ( ANXA5 , p = 0.005) and interleukin-6 ( IL-6 , p < 0.001) also differed among groups. After IBD vaccination, IBD-specific immunoglobulin A (IgA, p = 0.200) and IgG ( p = 0.065) responses were comparable; however, the alpha ( p < 0.001) and beta diversities ( p = 0.001) were significantly different among the groups. The JB00008 group showed higher Enterococcus and Bifidobacterium , with enrichment of pathways associated with iron complex transport systems ( p < 0.050). These findings suggest that JB00008 postbiotics may enhance intestinal barrier function and microbiota health without affecting growth, thereby supporting gut stability after vaccination. Furthermore, these results highlight the potential use of E. faecium JB00008 as a feed additive and vaccine adjuvant.